Eksistensi Grab Food Terhadap Omzet Bisnis Kuliner Di Kabupaten Lombok Timur - Sirrul Hayati; Siti Reuni Inayati (Universitas Hamzanwadi, 2022)
The development of information technology in the era of the industrial revolution 4.0, increasingly affects the order of life. Ease of ordering, time and cost efficiency make online transportation superior to conventional transportation. In 2019, the people of East Lombok were introduced to online transportation, namely Grab. From 2019 to 2020 the number of culinary businesses that have joined Grabfood is 183 businesses. This study aims to determine the effect of the existence of the Grabfood service in increasing the turnover of culinary sales. The research location was conducted in East Lombok, especially in the city of Selong. Determination of respondents as the selected data source using purposive sampling technique. Collecting data using observation, interview and documentation techniques. Qualitative data analysis: data reduction, data exposure, and drawing conclusions. According to the results of interviews, observations and data collection, the results show that the more users of e-commerce, the more culinary transactions increase. The existence or existence of online transportation grabfood is influential and has a big impact on the culinary business in East Lombok, especially in the city of Selong. Not only in terms of increasing turnover but also providing free promotional media to introduce the location and menu so that it can be known by the wider community